New Perspectives in the Studies on Endocannabinoid and Cannabis: 2-Arachidonoylglycerol as a Possible Novel Mediator of Inflammation - Takayuki Sugiura; Saori Oka; Maiko Gokoh; Seishi Kishimoto; Keizo Waku (Elsevier, 2004)
2-Arachidonoylglycerol is an endogenous ligand for the cannabinoid receptors. To date, two types of cannabinoid receptors (CB1 and CB2) have been identified. The CB1 receptor is assumed to be involved in the attenuation of synaptic transmission. On the other hand, the physiological roles of the CB2 receptor, which is abundantly expressed in several types of inflammatory cells and immunocompetent cells, have not yet been fully elucidated. Recently, we investigated in detail possible physiological roles of the CB2 receptor and 2-arachidonoylglycerol in inflammation. We found that 2-arachidonoylglycerol induces the activation of p42/44 and p38 mitogen-activated protein kinases and c-Jun N-terminal kinase; actin rearrangement and morphological changes; augmented production of chemokines in HL-60 cells; and the migration of HL-60 cells differentiated into macrophage-like cells, human monocytes, natural killer cells, and eosinophils. We also found that the level of 2-arachidonoylglycerol in mouse ear is markedly elevated following treatment with 12-O-tetradecanoylphorbol 13-acetate, which induces acute inflammation. Notably, the inflammation induced by 12-O-tetradecanoylphorbol 13-acetate was blocked by treatment with SR144528, a CB2-receptor antagonist. Similar results were obtained with an allergic inflammation model in mice. These results strongly suggest that 2-arachidonoylglycerol plays essential roles in the stimulation of various inflammatory reactions in vivo. Keywords:: cannabinoid, Δ9-tetrahydrocannabinol, 2-arachidonoylglycerol, anandamide, inflammation